Autoencoder-based three-factor model for the yield curve of Japanese government bonds and a trading strategy - Yoshiyuki Suimon; Hiroki Sakaji; Kiyoshi Izumi; Hiroyasu Matsushima (Journal of Risk and Financial Management, 2020)
Interest rates are representative indicators that reflect the degree of economic activity. The yield curve, which combines government bond interest rates by maturity, fluctuates to reflect various macroeconomic factors. Central bank monetary policy is one of the significant factors influencing interest rate markets. Generally, when the economy slows down, the central bank tries to stimulate the economy by lowering the policy rate to establish an environment in which companies and individuals can easily raise funds. In Japan, the shape of the yield curve has changed significantly in recent years following major changes in monetary policy. Therefore, an increasing need exists for a model that can flexibly respond to the various shapes of yield curves. In this research, we construct a three-factor model to represent the Japanese yield curve using the machine learning approach of an autoencoder. In addition, we focus on the model parameters of the intermediate layer of the neural network that constitute the autoencoder and confirm that the three automatically generated factors represent the "Level", "Curvature," and "Slope" of the yield curve. Furthermore, we develop a long-short strategy for Japanese government bonds by setting their valuation with the autoencoder, and we confirm good performance compared with the trend-follow investment strategy.
Keywords: 330; autoencoder; interpretability; machine learning; term structure of interest rates; yield curve